2015 4th International Conference on Advanced Computer Science Applications and Technologies (ACSAT) 2015
DOI: 10.1109/acsat.2015.51
|View full text |Cite
|
Sign up to set email alerts
|

Web User' Knowledge and Their Behavior towards Security Threats and Vulnerabilities

Abstract: Most of web users today are university students. They become more familiar with Information Security (IS) because it is a taught course in the university curriculum. However, there are many students whose level of awareness on this subject is still not enough considering the occurrence of security risks and their frequent usage of the internet. Many studies have been conducted to assess students and to raise their level of IS awareness. This study concerns about students' knowledge and their behaviour or actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Through these various readings, the researcher concluded that the community needs a training program aimed at raising the electronic security awareness of employees. In a study by researcher Aliaa Ahmed Aldosari [3] from the International Islamic University in Malaysia, a study was conducted on the Saudi community to assess the awareness level of security threats based on their knowledge, behavior, and culture. The researcher selected students from two universities in the eastern region of Saudi Arabia.…”
Section: First Axis: Cognitive Level Of Studentsmentioning
confidence: 99%
“…Through these various readings, the researcher concluded that the community needs a training program aimed at raising the electronic security awareness of employees. In a study by researcher Aliaa Ahmed Aldosari [3] from the International Islamic University in Malaysia, a study was conducted on the Saudi community to assess the awareness level of security threats based on their knowledge, behavior, and culture. The researcher selected students from two universities in the eastern region of Saudi Arabia.…”
Section: First Axis: Cognitive Level Of Studentsmentioning
confidence: 99%
“… Study & Year # of subjects Purpose of the study Alotaibi et al [19] , 2016 629 Detailed survey of the cybersecurity awareness among people in Saudi Arabia, with a variety of cases Innab et al [20] , 2018 116 Studied email phishing awareness and security training of employees in governmental and private organizations in Riyadh Elrasheed & Nadir [21] , 2017 132 Studied and assessed cybercrime risks and awareness in AlNamas city in Saudi Arabia, evaluated cybercrime threats, and prescribed ways to protect the security of the local community. AlSagri et al [24] , 2015 455 Built a survey to examine the general public's privacy awareness for online social networks such as Twitter, Facebook, and LinkedIn in Saudi Arabia Aldossary et al [25] , 2015 123 Studied the relationship between students' knowledge and behavior regarding security risks related to passwords, email, copyright and piracy Alzamil [26] , 2012 134 Explored the perception of employees and managers on information security awareness in some Saudi Arabian organizations Alarifi et al [22] , 2012 633 Examined the level of information security awareness among the Saudi general public, to address the level of information security awareness based on Saudi culture. Alzahrani and Alomar [23] , 2016 2325 Investigated the level of awareness regarding network security, password, and cloud computing …”
Section: Related Workmentioning
confidence: 99%
“…Recognition of rubbish heights in vessels to optimize the garbage collection courses [13][14] [15]. The figure2 mentions a glance about the growing rate of internet enabled devices.…”
Section: ) Managing Waste Materialsmentioning
confidence: 99%